(3caGjI GdYhGe ajeG jLH Ydjge ef Yde GdcdGes - (3GdaVGdj , eMeO Hf TGaYj GdaVGdj,J (B1236 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ eMeO Hf GdTGaYi GdaVGdi GdTGaYiSCdfi HYV GdENhGf Cf Chda dg QSGdI ai GdJhMjO aCLHJg Edi Pdc s
(3BNQgG (B:s
(3hjLH Cf jYde Cf Udi Gddg Ydjg hSde CHjV eTQH HMeQI Ydi eG bGdg HYVge JeJ HMeO Gddg hMSf Yhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B60s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(115d) s
Keywords: (3GdJhMjO hGdedd hGdfMds